A Comparative Study of Multi-grade Teaching on the Achievement Levels in Hindi and Mathematics of Second Standard in Government and NGO Schools - Arora, Rita; Poonam, (INDIAN EDUCATIONAL REVIEW, 2013)
India has been striving to achieve 100 per cent literacy in primary education. 86th amendment of the Indian Constitution makes education a fundamental right for all children aged 6-14 years. Sarva Shiksha Abhiyan and Right to Education (RTE) Act of April 2010 aim to achieve the goal of Universalisation of Elementary Education. But despite the enormous efforts, India still struggles with the challenges in achieving 100 per cent literacy even in the primary education. 59 million children out of 200 million children in India in the age group 6-14 years are not attending school even today. Multi-grade Teaching has emerged as an alternate system of education the world over to achieve the goal of Education for All. It has been defined variously but essentially it is an education system in which students of two or more adjacent grade levels are taught in one classroom by one teacher, i.e. technique of simultaneous teaching of more than one grade by a single teacher. It was intended to study the efficacy of Multi-grade Teaching vis a vis conventional methods of teaching. The study focused on the effects of Multi-grade teaching on the overall achievement levels of the students in Hindi and Mathematics. The Study was carried out on 1000 students of second standard from primary schools. The study also aimed at determining the classroom processes and awareness of teachers towards MGT. Normative survey method was used for the Study. Self-constructed and standardised achievement test in Hindi and Mathematics along with a Reading Proficiency Test and Classroom Process Index scale developed by Dr. Lalit Kishore were as tools for the Study.